Biotheory : life and death under capitalism - Di Leo, Jeffrey R.; Hitchcock, Peter (New York, NY : Routledge, 2020)
Forged at the intersection of intense interest in the pertinence and uses of biopolitics and biopower, this volume analyzes theoretical and practical paradigms for understanding and challenging the socioeconomic determinations of life and death in contemporary capitalism. Its contributors offer a series of trenchant interdisciplinary critiques, each one taking on both the specific dimensions of biopolitics and the deeper genealogies of cultural logic and structure that crucially inform its impress. New ways to think about biopolitics as an explanatory model are offered, and the subject of bios (life, ways of life) itself is taken into innovative theoretical possibilities. On the one hand, biopolitics is addressed in terms of its contributions to forms and divisions of knowledge; on the other, its capacity for reformulation is assessed before the most pressing concerns of contemporary living. It is a must read for anyone concerned with the study of bios in its theoretical profusions.
OCLC-licensed vendor bibliographic record.
Keywords: Biopolitics; Capitalism